ANALISIS SEKTOR UNGGULAN DI KABUPATEN MUSI BANYUASIN PROVINSI SUMATERA SELATAN DENGAN MENGGUNAKAN PENDEKATAN LOCATION QUOTIENT (LQ) DAN DYNAMIC LOCATION QUOTIENT (DLQ) - Peni Syahrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify the leading sectors and observe the shift in economic structure in Musi Banyuasin Regency, South Sumatra Province using the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods. The data used are secondary data on the GRDP of Musi Banyuasin Regency and South Sumatra Province for the period 2021–2024 obtained from the Central Statistics Agency (BPS). The results of the LQ analysis show that most of the economic sectors in Musi Banyuasin Regency are basic sectors with an LQ value > 1. This condition indicates that the current economic condition of Musi Banyuasin Regency is relatively stable and growing positively. Meanwhile, the results of the DLQ analysis < 1, namely the Mining and Quarrying sector, reflect a shift in the economy of Musi Banyuasin Regency which shows a slowdown in the relative growth rate compared to the provincial level, so that its role in the regional economy tends to decline and indicates a shift from dependence on natural resource-based sectors to secondary and tertiary sectors that are more dynamic and sustainable.